ATOPIC DERMATITIS - EARLY DIAGNOSIS AND PREVENTION - Fatima Khusnutdinovna Irsalieva, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Atopic dermatitis is a chronic, relapsing skin disease characterized by itching, dry skin, and eczematous inflammation. The main characteristics of atopic dermatitis are severe itching, a recurrent course, and typically early onset. The prevalence of the disease in children is 15–30%, with 45% of patients developing the condition within the first 6 months of life [1]. Despite the fact that today quite detailed recommendations for patient management have been developed, some patients (5–10%) experience a continuously recurring course of the disease, which is the cause of significant material costs for treatment and can also lead to disability and a sharp decline in the quality of life of children [2]. Atopic dermatitis (AD) has been known as a skin disease since ancient times and is mentioned in many historical chronicles of various civilizations around the world. Atopic dermatitis is characterized by a chronic, relapsing course, age-related evolution, and a wide variety of clinical symptoms and signs. The earliest mention of atopic dermatitis was made by the Roman historian Suetonius (69–140 AD). In his work "The Lives of the Twelve Caesars," he describes the manifestations of the disease in Emperor Augustus, emphasizing dry skin, intense itching, and the seasonality of its manifestations. Most dermatologists of the past, encountering the varied manifestations of atopic dermatitis, which varied significantly in the same patient at different ages, considered these manifestations to be independent diseases. It was only in 1892 that E. Besnier combined disparate skin diseases into a single disorder that “changes” its clinical picture with age.